1995
DOI: 10.1007/bf00294709
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for gastric cancer influencing clinical practice

Abstract: Despite a slow decline in the incidence of gastric cancer over the last 90 years, we can still expect to see over 100,000 patients die of this disease each decade in England and Wales. The 5-year survival rate has not improved during this century, which is largely due to the stage at diagnosis being unchanged. There are a number of prognostic determinants in gastric cancer which have clinical relevance. Age is an important determinant; patients under 40 years commonly have more advanced diffuse lesions than ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 44 publications
1
21
0
2
Order By: Relevance
“…32,33 Lymphatic involvement is one of the most important prognostic factors in gastric cancer. 12,34 The prognostic value of LR in the evaluation of lymph node status found in this study confirms the results from previous studies. 1,35,36 The extent of lymph node dissection to optimize the benefit to the patient is still controversial.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…32,33 Lymphatic involvement is one of the most important prognostic factors in gastric cancer. 12,34 The prognostic value of LR in the evaluation of lymph node status found in this study confirms the results from previous studies. 1,35,36 The extent of lymph node dissection to optimize the benefit to the patient is still controversial.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, for gastric cancer, as well as for other cancers, the prognostic value of these factors has been consistently recognized. 1,4,12,34,42,43 Neglecting them may lead to important problems in the interpretation of scientific results, including the difficulty of inferring therapeutic results for each patient individually, in addition to a morphological staging group, and the impossibility of ascribing different survival rates to the treatment, because clinical factors are not taken into account. 44 Several alternative models designed to improve the accuracy of prognostic estimates of gastric cancer patients are published in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the duration of symptoms has been considered as a relevant prognostic factor in several studies. At least 14 studies have evaluated this prognostic aspect but all showed that duration of symptoms was not related to poor outcome [19,32,[43][44][45][46][60][61][62][63][64][65][66][67] . It would have seemed obvious that the sooner a patient is treated for cancer, the better the prognosis will be.…”
Section: Duration Of Symptoms and Outcome Of Gastric Cancermentioning
confidence: 99%
“…A profundidade do tumor nas paredes do estômago é um dos principais fatores prognósticos no paciente com carcinoma gástrico (4,21,30) , daí a importância em defini-la no pré-operatório. A TC e a US podem visualizar o espessamento da parede gástrica e a infiltração de órgãos adjacentes, porém são pouco precisos para determinar a profundidade do tumor na parede do estômago.…”
Section: Discussionunclassified